MODEL PEMBELAJARAN PENDIDIKAN AGAMA ISLAM YANG EFEKTIF: SEBUAH KAJIAN PUSTAKA - Indah Rahayu (CV. Lafadz Jaya, 2026)
Islamic Religious Education (IRE) plays a strategic role in shaping the character and spirituality of learners; however, the effectiveness of its teaching is often hampered by the use of conventional teaching models that are insufficiently relevant to the demands of the digital age. This literature review aims to identify and analyse effective PAI learning models based on a synthesis of Islamic educational theory, modern learning theory, and the latest empirical findings. The method employed is a qualitative literature review using a descriptive-analytical approach. The research findings indicate that an effective PAI learning model is one capable of harmoniously integrating the three main philosophical dimensions, namely ta’lim (knowledge transfer), ta’dib (cultivation of manners), and tarbiyah (holistic development), whilst selectively adopting the principles of constructivism, humanism, and behaviourism. Models such as cooperative learning, problem-based learning (Problem-Based Learning), discussion (hiwar), and habit formation have proven effective in enhancing cognitive understanding and the internalisation of values. In the digital age, the integration of blended learning, flipped classroom, and Project-Based Learning models, enriched with interactive media and a contextual approach (Contextual Teaching and Learning), further optimises the relevance and impact of PAI learning. The success of implementing these models depends on teachers’ competence, technological infrastructure, supportive school policies, and authentic assessment systems. This study concludes that there is no universal model; PAI teachers need to develop a flexible and contextual eclectic approach. The practical implications of this study provide a conceptual framework for teachers and educational institutions to develop innovative and transformative Islamic Religious Education (IRE) practices capable of shaping a generation of Muslims who are outstanding, moderate, and of noble character in the 21st century.